METODE PELAKSANAAN INTEGRAL BRIDGE PADA PROYEK PEMBANGUNAN JALAN TOL SURABAYA-MOJOKERTO (SECTION P1-P25 PADA Sta 11+190 â 11+440) - , AZIZUR RAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Integral bridge is a bridge structure that created the segment and made without any movement between spans or between spans the abutments thus behave like a continuous structure. Bridge integral System consist of full integral and semi integral. Integral Bridge with spans less than 20 metre to The condition in Indonesia most optimum use reinforced concrete type with system of full integral, while if more than 20 metre more suggested to use type of prestress with semi integral System. Integral bridge is intended to avoid the problems of bridge maintenance is very expensive due to the penetration of water / dust through joint movement, can improve the comfort for road users, can be used for long spans, cramped work space, dense population conditions and construction cost savings and implementation, and easily implemented in the field. Implementation of integral bridge at the start of the bottom of the structure consists of a foundation of jobs in that extended into the column supporting the pile head. Between pile head is connected to the beams that hold the floor plate. Bridge integral structure is different from the other bridge structures, the difference lies in the structure of the column. Integral bridge columns generally have a relatively smaller diameter than the other bridge columns. Location integral to the implementation of the bridge construction project Surabaya-Mojokerto toll Sta 11 +190-11 +440 located in Bebekan roads. The structure consists of an integral bridge bore pile foundation diameter 80 cm, 80 cm diameter circular columns, pile head, mortar pad and bearing pad, precast beam length of 9.20 meters, diaphragm, and floor plate. Quality of the concrete used was the K-350.